A 3D model recovers its current location - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
Since the first publication (Reuther 1926: 17, pl.7a) until now, scholars had lost the current location of an exceptional object found at Babylon. It was found during regular excavations in the square 24/25 Q2, in a cassite house under the neo babylonian Southern Palace. It was given the inventory number 39274. In the excavations’ reports (Reuther 1926: 17, pl. 7a) the object was published without dimensions, without museum location and with a debated date. It has probably been lost since then. It is a special shaped vessel representing two entrances protected by two pairs of gardians. In the most recent analyses of the object (Muller 2001: 222; Battini 2017: 74 and 98-99), none could find its location. During my work in the Yale Babylonian Collection, I found it with great joy. It bears the number YBC 10 073 (https://collections.peabody.yale.edu/search/Record/YPM-BC-038695). Still searching for how it came into the collection, the discovery suggests a reexamination, especially since the dimensions were not known and only one drawing was published by Reuther. This is therefore an opportunity to publish new photos.